Negotiating Tolerance and Belief Boundaries in Islamic Religious Education: A Case Study of a Plural Public School in Indonesia - Dina Kurnia Al Rachimi; Adi Kasimiko; Alan Alda Nugroho; Mambaul Ngadhimah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
In increasingly diverse school environments, Islamic Religious Education (Pendidikan Agama Islam/PAI) is supposed to foster tolerance while upholding students' religious beliefs. However, tolerance is frequently portrayed as a normative ideal without any pedagogical direction for dealing with actual interreligious interactions. In a multiple public school, this study explores how PAI serves as a pedagogical space for negotiating tolerance and defining the parameters of interreligious participation. A qualitative case study was conducted in class XI-9 at SMAN 1 Babadan, Indonesia. Data were collected through semi-structured interviews with a PAI teacher, written reflections from two Muslim students and one non-Muslim student, classroom and school observations, and supporting documents. The findings reveal that students develop tolerance not only through classroom instruction but also through everyday interreligious interaction within the school community. School activities strengthen cooperation and mutual respect, while the teacher plays a central role in distinguishing social respect, epistemic openness, and ritual participation when responding to interreligious issues. The study concludes that tolerance becomes educationally meaningful when translated into contextual pedagogical practices that help students navigate real interreligious experiences without compromising their religious beliefs. These findings contribute to multicultural Islamic education by highlighting belief-boundary negotiation as a key pedagogical dimension of tolerance education in plural schools.